Family Support in Adherence to Oral Anti-Diabetic Medications among Patients with Type 2 Diabetes Mellitus - Hilyah, Dini; Kuswinarti, Kuswinarti; Ramadhanti, Julia (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Adherence to medication is an important aspect in type 2 diabetes mellitus management. One of the factors that determine medication adherence is family support. This study aimed to analyze the relationship between family support and adherence to oral anti-diabetic medications in patients with type 2 diabetes mellitus.Methods: This study was a quantitative, non-experimental correlational study with a cross-sectional method conducted in December 2022–January 2023 on patients with type 2 diabetes mellitus at the Pasirkaliki Public Health Center, Bandung City, Indonesia. The study used a minimal sampling method. Data collection analysis was performed using the SPSS program with the Chi-square test.Results: In total, 50 respondents were included, of whom the majority (n30; 60%) had good family support, whereas 17 (34%) had sufficient family support, and only 3 (6%) had poor family support. A good level of medication adherence was indicated by 39 (78%). There was a significant relationship between family support and adherence to oral anti-diabetic medications in type 2 diabetes mellitus (p=0.003).Conclusions: A good relationship between family support and adherence to oral anti-diabetic medications is crucial in enhancing quality of life and wellness among patients with type 2 diabetes mellitus. Research related to other factors that affect adherence to oral anti-diabetic medications warrant further studies.